IDENTIFICATION AND TEMPERATURE CONTROL OF HOT AIR GENERATION PROCESS FROM BIOMASS BURNER - Arisariyawong, Tanayos; Hattasat, Natchanan; Kanjanawong, Surasak; Bunsuk, Jinnawat; Kaewluan, Sommas (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The hot air generation from biomass burner is widely used, since it is a renewable, eliminate agricultural wastes and reduce environmental problems. The temperature of hot air is an important parameter in determining the stability and efficiency of the biomass burner. Therefore, this research presents the identification and temperature control of the hot air generation process from biomass burner. The identification of process is written as a mathematical model of first order differential equations. A PI controller is using to control the temperature of the hot air to meet the requirements. The experimental results shown that the developed mathematical model was able to simulate the system response as well. The PI controller can control the hot air temperature as needed with the average root mean square error of 2.23 oC